Structural dynamic behavior study of the kenyir hydropower station ungated-type spillway - Arbain A.; Zawawi M.H.; Mazlan A.Z.A.; Abas M.A.; Radzi M.R.M.; Hassani A. (American Institute of Physics Inc., 2023)
Frequency response function (FRF) and modal parameters including the natural frequency, damping ratio and mode shapes need to be studied in order to aid the monitoring process as well as to avoid the resonance to the structure. This is important since these measurements will be used as reference for any operational methods for the dam structure. This paper will discuss the structural dynamic analysis of one of the dam available in Malaysia which is Kenyir Dam (Sultan Mahmud Power Station) in Terengganu. The study has been conducted on the spillway section of the dam structure. The CAD model of the structure has been designed based on real size structure (1:1 scale) with the consideration of real build-in materials. A finite element (FE) model of the structure is then constructed in ANSYS Workbench software to run the analysis. Meshing sensitivity analysis has been conducted and the boundary condition has been set before performing the analysis. 30 natural frequencies have been determined and 6 most significant mode shapes are chosen to be discussed in this paper. For the FRF, all three axes, x, y and z-direction have the same dominant natural frequency value of 19.6Hz, where the highest deflection occurred at z-direction with 6.795 x 10-4 m. 2020 Author(s).